2020
DOI: 10.1101/2020.09.22.20199455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Norwich COVID-19 Testing Initiative: feasibility project evaluation

Abstract: Background There is a high prevalence of COVID-19 in university-age students, who are returning to university campuses. There is little evidence regarding the feasibility of universal, asymptomatic testing to control outbreaks in this population. This study aimed to pilot mass COVID-19 testing on a university research park, to assess the feasibility and acceptability of scaling up to all staff and students. Methods This was a cross-sectional feasibility study on a university research park in the East of Engl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In their study, Blaisdell et al [ 43 ] suggested that a two-phased universal testing strategy may be effective in minimizing transmission, and the experiences of the University of Texas and North Carolina University highlights the potential for rapid transmission on campus [ 12 , 44 , 45 ]. Gillam et al [ 18 ] proposed that repeated self-testing for COVID-19 using PCR is feasible and acceptable for a university population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, Blaisdell et al [ 43 ] suggested that a two-phased universal testing strategy may be effective in minimizing transmission, and the experiences of the University of Texas and North Carolina University highlights the potential for rapid transmission on campus [ 12 , 44 , 45 ]. Gillam et al [ 18 ] proposed that repeated self-testing for COVID-19 using PCR is feasible and acceptable for a university population.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that universal testing may have a significant impact on the control of the virus, depending on the ability of the location to implement other control measures [ 44 ], but universal testing and testing symptomatic people are not well studied as testing programs for COVID-19 at a university campus [ 18 ], and the type of test that would be the most useful in the university context considered is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Norwich in England said that asymptomatic testing helped control transmission and that repetitive self-testing, even for those without symptoms. 2 In the Philippines, there have been more than half a million cases almost a year since the country implemented community quarantine measures in March 2020. The national government’s effort to ‘test, trace and isolate’ has not been mainly prioritized, and therefore, not fully implemented.…”
mentioning
confidence: 99%
“…Our laboratory differs from other academic testing facilities that have been set up around the world 5,6 ; it has been established in collaboration with the DHSC to ensure that the results feed directly into the national Pillar 2 infrastructure, rather than being a 'stand-alone service' .…”
mentioning
confidence: 99%